The Matalaque Formation of southern Peru: new stratigraphie and geochemieal data - Cervantes Gárate, John (2005)
The Matalaque Formation crops out in the Western Cordillera of Southern Peru between 16°20' y 17°45 ' South Latitud. It was described initially by Marocco and del Pino (1966) in the lchufia sheet (department of Moquegua), extending southward to Carumas-Omate sector where it was described by Garcia (1978); in this area Vicente (1981) describes it as a lateral equivalent of the Murco Formation ln the Pachia and Palca region, Wilson and Garcia (1962) define a similar sequence (volcano-sedimentary) named Chulluncane Formation. Later Monge and Cervantes (2000), redefine this litho-stratigraphie sequence establishing is the same unit recognized in Ichufia (Matalaque). The objective of this paper is to contribute with new litho-stratigraph of the associated sedimentary basin that was deposited during the Aptiano-Albiano.